Identification of the MuRF1 Skeletal Muscle Ubiquitylome Through Quantitative Proteomics. Issue 4 (19th May 2021) - Baehr, Leslie M; Hughes, David C; Lynch, Sarah A; Van Haver, Delphi; Maia, Teresa Mendes; Marshall, Andrea G; Radoshevich, Lilliana; Impens, Francis; Waddell, David S; Bodine, Sue C
Abstract: MuRF1 (TRIM63) is a muscle-specific E3 ubiquitin ligase and component of the ubiquitin proteasome system. MuRF1 is transcriptionally upregulated under conditions that cause muscle loss, in both rodents and humans, and is a recognized marker of muscle atrophy. In this study, we used in vivo electroporation to determine whether MuRF1 overexpression alone can cause muscle atrophy and, in combination with ubiquitin proteomics, identify the endogenous MuRF1 substrates in skeletal muscle. Overexpression of MuRF1 in adult mice increases ubiquitination of myofibrillar and sarcoplasmic proteins, increases expression of genes associated with neuromuscular junction instability, and causes muscle atrophy. A total of 169 ubiquitination sites on 56 proteins were found to be regulated by MuRF1. MuRF1-mediated ubiquitination targeted both thick and thin filament contractile proteins, as well as, glycolytic enzymes, deubiquitinases, p62, and VCP. These data reveal a potential role for MuRF1 in not only the breakdown of the sarcomere but also the regulation of metabolism and other proteolytic pathways in skeletal muscle. Graphical Abstract: